Modelling thermocline storage for CSP yield assessment and process control simulation - Falchetta, Massimo; Binotti, Marco; Avallone, Fabrizio (AIP conference proceedings, 2019)
In view of the adoption of thermocline Thermal Energy Storage (TES) systems for Concentrated Solar Power (CSP) plants the thermocline behavior needs to be modeled to correctly predict the plant’s yearly energy yield and to specify and tune plant’s process control (e.g. solar field temperature control requirements, electric production scheduling based on estimation of the TES state of charge, etc.). Indeed the thermocline evolution influences the ratio between the nominal TES capacity and the effective one, therefore the potential degradation of the thermocline, when subject to arbitrary charge/discharge cycles, off-design temperature input from the solar field and/or incomplete charging cycles in periods or low Direct Normal Irradiation (DNI) must be taken into account. This paper illustrates the development of a thermocline TES dynamic model sufficiently accurate to predict the TES behavior but sufficiently simple to allow a fast execution of the simulation in the time domain. The TES model is implemented in MATLAB/Simulink environment in order to allow its integration into a whole-plant model comprising solar field, TES, power block and control logics. The objective is to simulate in time domain the behavior of a 1 MWe solar plant with a linear fresnel solar field, 4 hours of thermocline thermal storage and Organic Rankine Cycle (ORC) power block, actually under construction in the frame of the EU funded project (H2020) ORC-Plus. The model has been validated against available experimental data and results from other TES models. Some examples of TES model’s output with different DNI diurnal patterns are also shown.